Accurate Ranging Based on Transmission Line Channel Monitoring Image and Point Cloud Data Mapping. (21st May 2022) - Dai, Yongdong; Wang, Maofei; Mao, Feng; Yao, Jianguang; Wang, Shenyu
Abstract : Three-dimensional (3D) mapping of power lines is essential for power line inspection. Many remotely sensed data products like light detection and ranging (LiDAR) have been examined for power line surveys. More and more data are being obtained via photogrammetric measurements. This increases the need for the implementation of advanced processing techniques. In recent years, there has been a significant advancement in visualization techniques for power lines using unmanned aerial vehicle (UAV) platform photography. The most advanced of such imaging systems can create dense point clouds. However, the accuracy is very often unstable and dependent on the radiometric quality of images and the efficiency of the image processing technique. In this study, the two-dimensional information is obtained by photographing the real-time panorama of the transmission line channel using a 3D camera, and the three-dimensional information is acquired using laser radar technology. The three-dimensional point orientation of the target object and the transmission line is determined using the mapping relationship between two and three dimensions, the obtained data are calculated, and the calculation results are produced. The proposed method can solve the problem of the image sensor being unable to map spatial distance and can provide broad coverage of the transmission line channel and 24-hours accurate real-time remote monitoring.